edavis080106 edavis080106
  • 04-08-2022
  • Mathematics
contestada

irections: Simplify each expressio
25-(√16-1)-(3-9)²

Respuesta :

rvkacademic
rvkacademic rvkacademic
  • 04-08-2022

Answer:

-14

Step-by-step explanation:

[tex]\sqrt{16} = 4\\\\(\sqrt{16} - 1) = (4 -1) =3\\\\(3-9) = (-6)\\\\(3-9) ^2 = (-6)^2 = 36\\\\25 - 3 - 36 = 25 - 39 = -14\\[/tex]

Answer Link

Otras preguntas

Scarcity is the condition of not having enough goods and services to satisfy everyone's?
Historians of china have traditionally dated the beginning of Chinese civilization to the founding of the what??
Which equation has the same y-intercept as y=4x-3?a. y-3=x              b. y=8x+3    c. 3-y=4x      d. y=-3+8xWhich of the following is the equation of the line
Scarcity is the condition of not having enough goods and services to satisfy everyone's?
How were life forms affected by the rise in atmospheric oxygen levels that began 2.2 billion years ago?
How were life forms affected by the rise in atmospheric oxygen levels that began 2.2 billion years ago?
Scarcity is the condition of not having enough goods and services to satisfy everyone's?
Data are drawn from a symmetric and bell shaped distribution with a mean of 120 and a standard deviation of 5. There are 900 observations in the data set. What
find an equivalent expression without parentheses -(50x-15y+15)=
find an equivalent expression without parentheses -(50x-15y+15)=